2005
DOI: 10.3346/jkms.2005.20.3.421
|View full text |Cite
|
Sign up to set email alerts
|

Hypoadiponectinemia and Insulin Resistance are Associated with Nonalcoholic Fatty Liver Disease

Abstract: We investigated the association between nonalcoholic fatty liver disease (NAFLD) and plasma adiponectin levels and insulin resistance. We recruited study subjects among one hundred and eighty one persons who were examined abdominal ultrasound at routine screening tests. A standard interview (consumption of alcohol and medical history), physical examination (height, weight, waist circumference, and blood pressure), and biochemical study (lipid parameters, aminotransferases, fasting plasma glucose, fasting insul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
18
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 42 publications
7
18
0
1
Order By: Relevance
“…12 In this study, we observed that treatment with candesartan, an angiotensin-II receptor antagonist, was associated with a significantly decreased liver weight and ratio of liver weight to body weight, in addition to reduced lipid infiltration in the liver, reported the beneficial effect of the angiotensin receptor blocker in seven subjects with non-alcoholic steatohepatitis and hypertension. Histological assessment showed improvement of hepatic necro-inflammation in five patients, reduction of hepatic fibrosis in four individuals, and disappearance of iron deposition in two subjects.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…12 In this study, we observed that treatment with candesartan, an angiotensin-II receptor antagonist, was associated with a significantly decreased liver weight and ratio of liver weight to body weight, in addition to reduced lipid infiltration in the liver, reported the beneficial effect of the angiotensin receptor blocker in seven subjects with non-alcoholic steatohepatitis and hypertension. Histological assessment showed improvement of hepatic necro-inflammation in five patients, reduction of hepatic fibrosis in four individuals, and disappearance of iron deposition in two subjects.…”
Section: Discussionmentioning
confidence: 80%
“…14 In the present investigation, we found that serum adiponectin concentrations and hepatic expression levels of adiponectin mRNA were significantly higher in candesartan-treated mice than in control mice, suggesting that the angiotensin receptor blocker might alleviate NAFL through the increase of circulating adiponectin levels. Serum adiponectin levels are reduced under conditions of insulin resistance such as NAFL, 12 despite an elevated mass of fat cells. Delivery of recombinant adiponectin into mice with NAFL or alcoholic fatty liver has been shown dramatically to alleviate hepatomegaly and steatosis and to significantly attenuate inflammation and the increased levels of serum alanine aminotransferase.…”
Section: Discussionmentioning
confidence: 99%
“…[41][42][43] This association has remained significant in some 39,40 but not all studies after adjusting for BMI 38,43 or BMI and other risk factors. 44 In a study of 271 nondiabetic subjects in whom liver fat was measured by proton spectros- Figure 1. Reproduced with permission from Kotronen et al 25 copy, the correlations between liver fat and BMI, waist circumference, and intraabdominal fat were 0.47, 0.58, and 0.65, respectively (PϽ0.0001 for all).…”
Section: Waistmentioning
confidence: 99%
“…Another study in Taiwan, including 210 obese subjects, also demonstrated similar association between WC and fatty liver (multivariate logistic regression analysis, per 1-cm increase in WC, OR 1.10, 95% CI 1.04-1.16) [13] . A Korean study with 91 cases also found association between WC and NAFLD (per 1-cm increase in WC, OR 1.13, 95% CI 1.04-1.22) [14] . A Japanese study (n=129 individuals) reported an increase of WC increased with the severity of fatty liver [15] .…”
Section: Discussionmentioning
confidence: 87%